On the comparative advantage of tradable emission permits in a setting of uncertain abatement costs and market power: A case against the invariably pessimistic view - Clemens Heuson (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
Recent work has shown that Weitzman's policy rule for choosing price- versus quantity-based pollution control instruments under uncertainty is biased when the polluting firms possess market power (Heuson 2010). However, this study is restricted to emission standards and taxes, while tradable emission permits are ruled out since market power gives rise to strategic permit trading, which requires some separate effort in investigation. This paper aims at closing this gap and, in doing so, makes three main contributions. First, it provides the first-time full comparative analysis of the three most common pollution control instruments stated above which takes into account two features that are frequently given in actual regulation settings, namely market power of polluting firms and uncertain abatement costs from the regulator's perspective. Second, the paper reveals a new form of strategic permit trading that may arise even though the permit market is perfectly competitive. Finally, the rather pessimistic view concerning the impact of market power on the comparative advantage of tradable emission permits, which dominates in the literature so far, is put into context.
Keywords: D89; L13; Q58; 330; external diseconomies of pollution; emission standards; tradable emission permits; emission taxes; uncertainty; Cournot competition; market power; strategic behaviour